Field based analysis of vegetation and climate impacts on the hydrological properties of urban vegetated slope - Manoj Kumar; Khresna Paramaputra; Ahmad Mousa; Sih Ying Kong; Ankit Garg; Vivi Anggraini (Scientific Reports)
Abstract The presence of vegetation in urban soil is both visually appealing and environmentally beneficial. Vegetation contributes to changes in soil water content (SWC) and soil suction (SS) through transpiration. These changes ultimately affect slope stability, soil erosion, runoff generation, and water infiltration. This study closely examines the impact of tree canopy covers on SWC and SS dynamics in an urban slope site with a diverse mix of vegetation (trees and grass) in a tropical region. Field monitoring revealed that slope areas with higher tree canopy cover consistently exhibited lower SWC and higher SS at shallower depths, highlighting the stabilizing effects of vegetation. During wet periods, the difference in SWC between high and low canopy cover areas increased by 36% compared to dry periods, emphasizing the role of canopy cover in regulating soil moisture under varying climatic conditions. Furthermore, stations with lower canopy cover demonstrated a stronger correlation between SWC and relative humidity (R values of 0.64 in dry and 0.71 in wet periods) than those with higher canopy cover (R values of 0.57 in dry and 0.63 in wet periods), indicating distinct soil moisture retention patterns based on canopy density. These findings underscore the critical role of tree canopy cover in controlling SWC and SS dynamics, particularly for urban slope stability and sustainable landscape management.